2012
DOI: 10.1084/jem.20112272
|View full text |Cite
|
Sign up to set email alerts
|

Deletion and anergy of polyclonal B cells specific for ubiquitous membrane-bound self-antigen

Abstract: Both deletion and anergy shape B cell tolerance to membrane-bound antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
193
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(206 citation statements)
references
References 33 publications
9
193
4
Order By: Relevance
“…Recent studies tracking autoreactive B-cell populations in the wild-type repertoire have argued that for some classes of self-antigens, B-cell tolerance is achieved not by deletion or anergy but largely through a lack of cognate T-cell help (40). Overall, these data support a model where thymic B cells couple a broad recognition of self-antigens with an enhanced antigen-presentation capacity to purge cognate T cells from the developing repertoire.…”
Section: Igmmentioning
confidence: 72%
“…Recent studies tracking autoreactive B-cell populations in the wild-type repertoire have argued that for some classes of self-antigens, B-cell tolerance is achieved not by deletion or anergy but largely through a lack of cognate T-cell help (40). Overall, these data support a model where thymic B cells couple a broad recognition of self-antigens with an enhanced antigen-presentation capacity to purge cognate T cells from the developing repertoire.…”
Section: Igmmentioning
confidence: 72%
“…For antigen-specific B cell experiments, a 14-kDA truncated carboxy terminus of PyMSP1 was cloned, purified, biotinylated, and tetramerized with streptavidin-PE (Prozyme) as previously described (38,96). Decoy reagent to detect B cells specific for tetramer components was constructed as previously described (17,43).…”
Section: Methodsmentioning
confidence: 99%
“…Because cGAS has been reported to affect the T-independent B cell response (15), we hypothesized that the loss of parasite control we had observed in cGAS -/-mice could be associated with a loss of early plasmablast formation in a T cell-independent fashion. To examine the antigen-specific B cell response, we used a B cell tetramer comprising the C-terminal portion of the merozoite surface protein 1 (MSP1) protein of P. yoelii (17,38). Antibodies against MSP1 are associated with clinical immunity in endemic populations (39,40) and murine models of Plasmodium infection (41,42).…”
Section: Cd11bmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-clinical and clinical studies of SUD vaccines showed that post-immunization anti-drug Ab levels and affinity vary greatly across subjects, but the cause of such variability is not clear. 10 Before and after immunization, the number of antigen-specific B and T cells in the total lymphocyte repertoire varies in individual mice 33,[36][37][38][39][52][53][54][55][56][57][58] and in human subjects. 59,60 Consistently, individual variability of similar magnitude has been found in the polyclonal hapten-specific B cell population in blood, peripheral lymph nodes and spleen of various mouse strains, before and after immunization with vaccines for oxycodone and nicotine.…”
Section: Pre-clinical Developmentmentioning
confidence: 99%